Sensory‐based conservation of seabirds: a review of management strategies and animal behaviours that facilitate success. (2nd November 2016) - Friesen, Megan R.; Beggs, Jacqueline R.; Gaskett, Anne C.
ABSTRACT: Sensory‐based conservation harnesses species' natural communication and signalling behaviours to mitigate threats to wild populations. To evaluate this emerging field, we assess how sensory‐based manipulations, sensory mode, and target taxa affect success. To facilitate broader, cross‐species application of successful techniques, we test which behavioural and life‐history traits correlate with positive conservation outcomes. We focus on seabirds, one of the world's most rapidly declining groups, whose philopatry, activity patterns, foraging, mate choice, and parental care behaviours all involve reliance on, and therefore strong selection for, sophisticated sensory physiology and accurate assessment of intra‐ and inter‐species signals and cues in several sensory modes. We review the use of auditory, olfactory, and visual methods, especially for attracting seabirds to newly restored habitat or deterring birds from fishing boats and equipment. We found that more sensory‐based conservation has been attempted with Procellariiformes (tube‐nosed seabirds) and Charadriiformes (e.g. terns and gulls) than other orders, and that successful outcomes are more likely for Procellariiformes. Evolutionary and behavioural traits are likely to facilitate sensory‐based techniques, such as social attraction to suitable habitat, across seabird species. More broadly, successful application of sensory‐based conservation to other at‐risk animal groups is likely to be associated with these behavioural and life‐history traits: coloniality, philopatry, nocturnal, migratory, long‐distance foraging, parental care, and pair bonds/monogamy.